Training Future Science Librarians: A Successful Partnership Between Academia and the United States Environmental Protection Agency - Kristen Conahan Roland (Issues in Science and Technology Librarianship)
The School of Information and Library Science at the University of North Carolina at Chapel Hill has operated a library for the United States Environmental Protection Agency in Research Triangle Park, NC for more than 25 years. The unique contract partnership provides the opportunity for master's level students to acquire practical experience working in a science library while taking classes. More than 280 former student interns have continued onto careers in academic, corporate/special, public, and school libraries, or have taken information science-oriented positions with different companies across the country. This network of former interns speaks to the value of providing the opportunity for practical experience during the master's degree process, and demonstrates that privatization or outsourcing of services can be a "win-win" situation for those involved.